STRATEGI PENANAMAN DISIPLIN ANAK USIA 4-5 TAHUN DI PAUD SAI CERIA SEJUAH KABUPATEN SANGGAU - Agnes Hilna; Muhammad Ali; Desni Yuniarni (Universitas Tanjungpura, 2022)
This study aims to describe the strategy of inculcating discipline in children aged 4-5 years in Sai Ceria Sejuah Early Childhood Education, Sanggau Regency. the sample in this study was class X students totaling 3 students, the subject was taken based on the needs in the study, namely the class A teacher totaling 1 person at PAUD Sai Ceria Sejuah Sanggau Regency, the research method used was descriptive with a qualitative approach as for the technique data collection using observation techniques, interviews and documentation. The results showed: 1) the strategy of cultivating discipline through exemplary, the teacher applied an exemplary strategy by giving examples of disciplined behavior to children such as taking off shoes before entering class, storing shoes on the shelves provided, putting bags on the shelves, and tidying up stationery and accessories. used toys. 2) exemplary strategy through stories, the teacher tells stories using media in the form of printed story books with the theme of discipline. 3) the strategy of inculcating discipline through habits, for example, the teacher familiarizes children with taking off their shoes before entering class and keeping the shoes on the shelf.